2010
DOI: 10.4061/2011/208634
|View full text |Cite
|
Sign up to set email alerts
|

New Proteins Found Interacting with Brain Metallothionein‐3 Are Linked to Secretion

Abstract: Metallothionein 3 (MT-3), also known as growth inhibitory factor (GIF), exhibits a neuroinhibitory activity. Our lab and others have previously shown that this biological activity involves interacting protein partners in the brain. However, nothing specific is yet known about which of these interactions is responsible for the GIF activity. In this paper, we are reporting upon new proteins found interacting with MT-3 as determined through immunoaffinity chromatography and mass spectrometry. These new partner pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 72 publications
(98 reference statements)
1
22
0
Order By: Relevance
“…In addition, MT-III is known as a neuronal growth inhibitory factor that interacts with many proteins. 42 Taken together, our results indicated that MT-III may exert an important neuroprotective influence over retinal photoreceptor cells, with antioxidant activity and/or other protection mechanisms. Previously, we reported that MT-II was increased in NMDAtreated retina, especially ganglion cell layer (GCL) and inner plexiform layer, and that the GCL in MT-I/II-deficient mice exhibited increased vulnerability to NMDA.…”
Section: Discussionmentioning
confidence: 70%
“…In addition, MT-III is known as a neuronal growth inhibitory factor that interacts with many proteins. 42 Taken together, our results indicated that MT-III may exert an important neuroprotective influence over retinal photoreceptor cells, with antioxidant activity and/or other protection mechanisms. Previously, we reported that MT-II was increased in NMDAtreated retina, especially ganglion cell layer (GCL) and inner plexiform layer, and that the GCL in MT-I/II-deficient mice exhibited increased vulnerability to NMDA.…”
Section: Discussionmentioning
confidence: 70%
“…2000; Uchida et al. 2002; El Ghazi et al. 2010) and internalized by target cells through lipid‐raft‐dependent endocytosis (Hao et al.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that up-regulation of astrocytic MT-I may be relevant to neuron-astroglial communication. Several reports suggest that MT can be released from cultured cells under various conditions (Trayhurn et al 2000;Uchida et al 2002;El Ghazi et al 2010) and internalized by target cells through lipid-raft-dependent endocytosis (Hao et al 2007). We also found that MT-I was released from astrocytes and internalized by neurons in vitro (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Of four isoforms (Mt1-4), metallothionein-3 (Mt3) is most prominently expressed in the central nervous system (16,17); it is also expressed in cultured astrocytes (18 -22). Mt3 binds many different proteins, including actin (23,24). However, the biological function of Mt3, especially regarding the actin-Mt3 binding, has not been characterized.…”
mentioning
confidence: 99%